Factivity and subject extraction in Jordanian Arabic - Jarrah, Marwan (Lingua, 2019)
This paper investigates subject extraction from embedded clauses in Jordanian Arabic (JA). Firstly, it shows that JA maintains the division between factive vs. non-factive verbs with respect to (subject) extraction. We argue that non-factive clausal complements are not islands for extraction, and, hence, their subject can undergo movement to the left periphery of the main clause. We use Starke's (2001) proposal of Relativized Minimality to account for the ensuing restriction that bans the object and/or locative adjuncts of the factive clausal complement to appear pre-verbally (while the subject is extracted). We propose that this restriction is due to the richly-featured content of the subject wh-word that acts as a barrier against the movement of elements that fall under its c-command domain. As for factive clausal complements (i.e., embedded under factive verbs), we prove that such complements are strong islands for extraction. We follow Kiparsky and Kiparsky (1970) and related works, that factive complements are, with updated terminology, DPs which are absolute islands in Arabic. With this being the case, this paper challenges several recent approaches to factive complements that have argued either for a reduced left periphery for factive complements (e.g., Haegeman, 2006; de Cuba, 2007) or for the presence of an operator that has the effect to block movement out of these clauses (e.g., Zubizaretta, 2001; Haegeman, 2012).